2021
DOI: 10.1002/jcsm.12872
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Modified Patient‐Generated Subjective Global Assessment as a nutritional assessment tool in cancer patients

Abstract: Background Completing Patient-Generated Subjective Global Assessment (PG-SGA) questionnaires is time consuming. This study aimed to develop and validate an easy-to-use modified PG-SGA (mPG-SGA) for cancer patients. Methods Seventy professionals assessed the content validity, comprehensibility, and difficulty of the full PG-SGA. A survey including the PG-SGA and other questionnaires was completed by 34 071 adult hospitalized cancer patients with first cancer diagnosis or recurrent disease with any tumour comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Our present data also showed that there is a close association between the PG-SGA scores and PA in lung The KPS is widely used to assess the functional status of cancer patients. It has good predictive validity for the survival of lung cancer patients [21,54]. The PA has also been associated with the functional status of patients [22] and with a lower KPS score.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our present data also showed that there is a close association between the PG-SGA scores and PA in lung The KPS is widely used to assess the functional status of cancer patients. It has good predictive validity for the survival of lung cancer patients [21,54]. The PA has also been associated with the functional status of patients [22] and with a lower KPS score.…”
Section: Discussionmentioning
confidence: 88%
“…The PG-SGA is a widely used nutritional assessment tool for cancer patients and has been validated in patients with lung cancer [51], gastric cancer [52], colorectal cancer [53] and other cancers [54] in Chinese populations. A study by Abe et al demonstrated that the PA showed the best association with the PG-SGA in terms of sensitivity [55].…”
Section: Discussionmentioning
confidence: 99%
“…[27] The mPG-SGA was built from the PG-SGA by removing the physical examination and questions about metabolic demand. [25] Thus, the mPG-SGA is a more subjective tool for nutritional assessment. In the early stages of disease, patients may feel uncomfortable, but a physical examination may not reveal obvious positive signs.…”
Section: Tablementioning
confidence: 99%
“…[23] Thus, the abridged scored PG-SGA and the mPG-SGA have been developed to improve its performance, and these have also been assessed in Chinese patients. [24,25] In the present study, we aimed to examine the validity of the GLIM criteria for identifying malnutrition compared with the established PG-SGA and mPG-SGA in Chinese cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, involuntary WL is an important prognostic feature in patients with cancer 12,13 . In addition, involuntary WL is an important criterion among several commonly used nutritional screening tools in clinics 7,14 . Involuntary WL can be a prognostic marker for cancer patients, predicting poor survival and increased morbidity.…”
Section: Introductionmentioning
confidence: 99%